Influences of parents, close friends and classmates on four co-existing oral health practices in Saudi male teenagers. (17th February 2017) - El Tantawi, Maha; Bakhurji, Eman; Al-Ansari, Asim; Al-Khalifa, Khalifa S.; AlSubaie, Abdulelah
Abstract: Objective: The objective of this study is to investigate the association between oral health practices and similar practices adopted by parents, close friends and classmates in a group of Saudi male teenagers. Material and methods: A cross-sectional study was conducted in Dammam, Saudi Arabia, in 2016 including 12–14-year-old intermediate school students ( n = 478). A questionnaire assessed socioeconomic background, whether participants, their parents, close friends and classmates brushed twice daily, used tobacco, snacked on sugary foods or sugary drinks and perceiving a supportive classroom environment. Univariate and multivariate logistic regression models assessed the association of parents', close friends', classmates' practices and classroom support with participants' four practices, controlling for socioeconomic factors. Results: The response rate was 93.9%. In multivariate regression, close friends' practices had a strong significant association with teenagers' tooth brushing (OR = 4.45; 95%CI = 1.09, 18.12), tobacco use (OR = 5.63; 95%CI = 3.44, 7.88), snacking on sugary foods (OR = 14.42; 95%CI = 7.89, 21.89) and sugary drinks (OR = 7.05; 95%CI = 5.97, 9.20). The percentages of classmates perceived to brush their teeth and use tobacco were significantly associated with the respective practices in teenagers (OR = 1.03 and 1.02). Fathers' snacking on sugary drinks was significantly associated with that of the teenagers (OR = 4.04; 95%CI= 1.03, 15.85). Conclusions : In early adolescence, four oral health practices of Saudi males were associated with those perceived to be adopted by their close friends. Fathers' use of sugary drinks was also significantly associated with that of teenagers.